Antithrombotic Therapy for Atrial Fibrillation: CHEST Guideline and Expert Panel Report - Lip, Gregory Y H; Banerjee, Amitava; Boriani, Giuseppe; Chiang, Chern En; Fargo, Ramiz; Freedman, Ben; Lane, Deirdre A; Ruff, Christian T; Turakhia, Mintu; Werring, David; Patel, Sheena; Moores, Lisa (Chest, 2018)
The risk of stroke is heterogeneous across different groups of patients with atrial fibrillation (AF), being dependent on the presence of various stroke risk factors. We provide recommendations for antithrombotic treatment based on net clinical benefit for patients with AF at varying levels of stroke risk and in a number of common clinical scenarios. Systematic literature reviews were conducted to identify relevant articles published from the last formal search perfomed for the Antithrombotic and Thrombolytic Therapy: American College of Chest Physicians Evidence-Based Clinical Practice Guidelines (9th Edition). The overall quality of the evidence was assessed using the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) approach. Graded recommendations and ungraded consensus-based statements were drafted, voted on, and revised until consensus was reached. For patients with AF without valvular heart disease, including those with paroxysmal AF, who are at low risk of stroke (eg, CHA DS -VASc [congestive heart failure, hypertension, age ≥ 75 (doubled), diabetes, stroke (doubled)-vascular disease, age 65-74 and sex category (female)] score of 0 in males or 1 in females), we suggest no antithrombotic therapy. The next step is to consider stroke prevention (ie, oral anticoagulation therapy) for patients with 1 or more non-sex CHA DS -VASc stroke risk factors. For patients with a single non-sex CHA DS -VASc stroke risk factor, we suggest oral anticoagulation rather than no therapy, aspirin, or combination therapy with aspirin and clopidogrel; and for those at high risk of stroke (eg, CHA DS -VASc ≥ 2 in males or ≥ 3 in females), we recommend oral anticoagulation rather than no therapy, aspirin, or combination therapy with aspirin and clopidogrel. Where we recommend or suggest in favor of oral anticoagulation, we suggest using a non-vitamin K antagonist oral anticoagulant drug rather than adjusted-dose vitamin K antagonist therapy. With the latter, it is important to aim for good quality anticoagulation control with a time in therapeutic range > 70%. Attention to modifiable bleeding risk factors (eg, uncontrolled BP, labile international normalized ratios, concomitant use of aspirin or nonsteroidal antiinflammatory drugs in an anticoagulated patient, alcohol excess) should be made at each patient contact, and HAS-BLED (hypertension, abnormal renal/liver function [1 point each], stroke, bleeding history or predisposition, labile international normalized ratio, elderly (0.65), drugs/alcohol concomitantly [1 point each]) score used to assess the risk of bleeding where high risk patients (≥ 3) should be reviewed and followed up more frequently. Oral anticoagulation is the optimal choice of antithrombotic therapy for patients with AF with ≥1 non-sex CHA DS -VASc stroke risk factor(s).